Measurement of Demand Uncertainty in the Wine Supply Chain; [Medição de Incerteza de Demanda Da Cadeia de Suministro Do Vinho]; [Medición de Incertidumbre de Demanda de la Cadena de Suministro del Vino] - Vargas-Norambuena, J (Institute of Advanced Studies, University of Santiago de Chile, 2025)
Supply chains face increased uncertainty, which must be considered in tactical and operational decisions. There is a gap between the models proposed in research and actual practice. The objective of this research is to bridge this gap by providing findings in product classification based on the measurement of supply chain uncertainty. A case study of a winery in Chile is presented and empirical methods of product classification are reviewed. Two qualitative methods and one quantitative method are applied to measure the uncertainty of product demand. It is concluded that the quantitative method is superior in the operational and tactical decisions of the supply chain. The novelty lies in the application of a 2x2 matrix graphic quantitative method based on demand behavior that classifies products in a way that is useful for an integrated inventory management model. This article opens the door to future research that replicates this methodology in other industries with real cases to reduce the gap between theory and practice. © 2025 Institute of Advanced Studies, University of Santiago de Chile. All rights reserved.